Development of an Advanced Zinc Air Flow Battery System (Phase 2) - (:unkn) unknown (My University, 2020)
A zinc-air battery is the promising energy storage technology for large-scale energy storage applications due to its low cost, environmental friendliness, and high energy density. However, the electrically rechargeable zinc−air batteries suffer from poor energy efficiency and cycle life because of critical problems such as passivation, dendrite growth, and hydrogen evolution reaction. The proliferation of zinc−air batteries is limited. The zinc-air flow battery combines the advantages of both a zinc-air battery and a redox flow battery. This combination permits the zinc-air flow battery to compete with the current leading battery technologies in the marketplace. A rechargeable Zn-air flow battery with an automatic control system was designed and prototyped in our previous researches. In this study, the engineering aspects of the Zn-air flow battery system have been investigated. The reactor was re-designed and optimized. The non-reacted "dead zinc" problems and the deformation of the air cathode were solved in the Gen 2 design. The reactor's electrochemical performance was tripled, which benefited from applying the additive manufacturing processes (3D print) in the mechanical design. The air cathode fabrication process parameters were investigated, including the thickness, the binder content, and the expanded graphite content of the active layer. The 0.2mm was chosen as the desired thickness considering the efficiency of material and the fabrication's easiness. The PTFE content was determined as 5%, and expanded graphite content was 10% in the active layer for the balance of the electronic conductivity and tenacity. The LabVIEW based battery management system build-up and control algorithm was discussed.
Keywords: Battery; Flow battery; Zinc air